Real-world data on change in work productivity, activity impairment, and quality of life in patients with psoriatic arthritis under anti-TNF therapy: a postmarketing, noninterventional, observational study - Karadag, Omer; Dalkilic, Ediz; Ayan, Gizem; Kucuksahin, Orhan; Kasifoglu, Timucin; Yilmaz, Neslihan; Kalyoncu, Umut (Springer London Ltd, 2022)
Objectives To understand change in work productivity, activity impairment, quality of life (QoL), and disease activity in patients with psoriatic arthritis (PsA) receiving anti-tumor necrosis factor (anti-TNF) treatment. Method One hundred twenty patients with PsA receiving anti-TNF therapy were recruited to this noninterventional, observational study. Work disability was assessed via the Work Productivity and Activity Impairment (WPAI) questionnaire and disease activity was calculated via the 28-joint Disease Activity Score using C-reactive protein (DAS28-CRP) and Disease Activity Index for Psoriatic Arthritis with 28 joints (DAPSA28) score. Patient-reported outcomes (PROs), from visual analog scores and Health Assessment Questionnaire-Disability Index scores, were evaluated to understand the clinical effectiveness at baseline and every 3 months until the month-9 final visit. The American College of Rheumatology (ACR)20/50/70 response criteria were assessed at month 9. Results A total of 120 patients (females, n = 73) were enrolled in the study. Mean (SD) age and disease duration were 41.6 +/- 11.1 years and 6.9 +/- 6.5 years, respectively. The most commonly used TNF alpha inhibitor was adalimumab (42.4%), followed by etanercept (25.8%). All WPAI questionnaire parameters were reduced at the follow-up visits compared with baseline (p < 0.001 for all). PROs and disease activity indicators (DAS28-CRP and DAPSA28) significantly improved during the course of anti-TNF treatments (p < 0.001 for all). Additionally, ACR20/50/70 responses were determined as 86.8%, 63.7%, and 41.8% of patients at the month-9 visit. Conclusions The real-world data in PsA patients receiving anti-TNF treatment showed improvement in WPAI, QoL, and disease activity over 9 months of treatment.
Keywords: Anti-TNF; ACR20/50/70; DAPSA28; DAS28; Psoriatic arthritis; Work disability